2009
DOI: 10.1128/ec.00352-08
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Cryptococcus neoformans Spores Reveal a Critical Role for Capsule Biosynthesis Genes in Spore Biogenesis

Abstract: Spores are essential particles for the survival of many organisms, both prokaryotic and eukaryotic. Among the eukaryotes, fungi have developed spores with superior resistance and dispersal properties. For the human fungal pathogens, however, relatively little is known about the role that spores play in dispersal and infection. Here we present the purification and characterization of spores from the environmental fungus Cryptococcus neoformans. For the first time, we purified spores to homogeneity and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
95
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 52 publications
1
95
0
Order By: Relevance
“…No sterigmata on the basidia were observed in these crosses, similar to the findings for C. neoformans. Different C. gattii molecular types were compared to spores produced by serotype A and D strains (see findings are in accord with data from previous and recent studies (3,47) and reveal additional insights into spore morphology. Spore germination signals.…”
Section: Resultssupporting
confidence: 70%
“…No sterigmata on the basidia were observed in these crosses, similar to the findings for C. neoformans. Different C. gattii molecular types were compared to spores produced by serotype A and D strains (see findings are in accord with data from previous and recent studies (3,47) and reveal additional insights into spore morphology. Spore germination signals.…”
Section: Resultssupporting
confidence: 70%
“…The resulting plasmid encodes a histone 3 promoter-driven enhanced green fluorescent protein (EGFP) with an 80-amino-acid NLS and a nourseothricin resistance (NAT r ) cassette. This integrating plasmid was then transformed via bombardment into C. neoformans B3502 to generate strain CHY3135 (47). This strain produces bright GFP that is localized to the nucleus.…”
Section: Methodsmentioning
confidence: 99%
“…All were handled using standard techniques and media as described previously (45,46). Spores were purified from crosses using density gradient purification as described previously (47). Briefly, mixed haploid yeast cells of opposite mating types (CHY3515 and CHY3516) were spotted onto V8 solid medium at a ratio of 1:1 and a total optical density at 600 nm (OD 600 ) of 1.0.…”
Section: Methodsmentioning
confidence: 99%
“…grubii strains (4). Our initial biochemical characterization of C. neoformans spores revealed that they possessed a cell surface composition different from yeast but physical properties similar to other fungal spores (4). These observations led us to speculate that, like other pathogenic fungi, the infectious life cycle of C. neoformans might include an infectious spore form that transitions into a pathogenic form in the lungs.…”
mentioning
confidence: 99%